Appropriation and Efficiency: A Revision of the First Theorem of Welfare Economics - Louis Makowski; Joseph M. Ostroy (American Economic Review, 1995)
The First Theorem of Welfare Economics rests on the assumption that individuals have neither price-making nor market-making capacities. We offer a revision in which individuals have such capacities. The revision emphasizes two keys for market efficiency: (i) the need to align private rewards with social contributions–called full appropriation, and (ii) the need for an assumption to counter the possibility of coordination failures in the choice of produced commodities–called noncomplementarily. We also emphasize that information about prices of unmarketed commodities involves decentralized knowledge available only to product innovators and that pecuniary externalities are important potential sources of market failure.